Liquid Wisdom: Conceptual Metaphors and the Cognitive Ecology of Political Rhetoric in 7th Century Islamic Conflict - M. Abood, Dr. Ayaad (Basra studies journal, 2026)
This study examined the conceptual metaphors employed by Imam Ali during the Battle of Siffin (657 CE). Through systematic rhetorical analysis of Imam Ali’s speeches and letters, the major metaphorical schemas that structured his political-military discourse were identified and categorized by the research. The findings revealed sophisticated conceptual systems rather than isolated figurative expressions, with each metaphorical domain—water/thirst, light/darkness, path/journey, body/physical, animal, fire/heat, and commercial/exchange—serving as comprehensive cognitive frameworks through which complex political and theological concepts were rendered accessible to his audience. This analysis demonstrated how Imam Ali’s metaphors exhibited strategic adaptation to changing military circumstances, integrated theological and political dimensions, and frequently created conceptual space for reconciliation despite the conflict context. The remarkable sophistication of these 7th century metaphorical systems challenged simplistic notions of metaphorical development and offered valuable insights for contemporary understanding of political-religious discourse. This study provides the first ecology-aware, CMT account of Siffīn that models metaphor as integrated, adaptive systems linking ethical–theological commitments to tactical reasoning.